Radiographic and Functional Outcomes following Knee Arthrodesis Using the Wichita Fusion Nail - McQuail, Paula; McCartney, Ben; Baker, Joseph; Green, James; Keogh, Peter; Kenny, Patrick (The Journal of Knee Surgery, 2018)
The purpose of this study was to report both the radiographic and functional outcomes of patients undergoing knee arthrodesis with the Wichita Fusion Nail (WFN) within the Republic of Ireland and compare the results to existing literature. Patient charts and radiographs were reviewed on all patients who had a WFN implanted in Ireland to date. Patients were invited to complete a Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score as a functional assessment. Twenty-three patients were identified. Patients had an average of 8 (range: 0–26) knee surgeries prior to arthrodesis. The most common indication was failed arthroplasty due to recalcitrant infection (69.5%). Successful fusion occurred in 60.8% of patients. The mean time to fusion was 9.21 months. The mean WOMAC score was 58.55 with a range of 31 to 96. We found a rate of arthrodesis lower than that reported in other published series. However, the rate of major complications was comparable to those published previously, reflecting the often-challenging patient cohort. Our study shows that the WFN should not be viewed as a near-universally successful option to salvage an unreconstructable knee.
Keywords: arthrodesis; knee arthroplasty; fusion; Wichita Fusion Nail